Major food sources of polyphenols in Serbian adult population - Rajić, Jelena; Šobajić, Sladjana; Vidović, Bojana; Bašić, Jasmina; Živković, Vladimir (Archives of Pharmacy, 2022)
A considerable interest has been developed over the years for fruits and vegetables consumption due to their potential biological and health promoting effects. This effect is attributed to antioxidants. Among the most important natural antioxidants are secondary plants metabolites, polyphenols. Epidemiological studies indicate that an increase in the consumption of fruits and vegetables is associated with a decrease in the incidence of various diseases. The aim of this work was to estimate the intake of polyphenols in the adult population of the Republic of Serbia based on literature data on polyphenol content in certain foods and intake data obtained from the Bulletin - Household Budget Survey, 2019 (Statistical Office of the Republic of Serbia), as well as literature data on intake. Based on literature data on the content of polyphenols in different food groups, it was determined that the following food groups can be sources of polyphenols in the diet of the Serbian adult population: vegetables, fruits, coffee, tea, cacao, chocolate, wine, nuts, and fruit juices. Using the Statistical Office of the Republic of Serbia data, as well as the literature data on the content of polyphenols in foods that are the major sources of polyphenols in the diet of the adult Serbia population, the polyphenol intake was estimated. The daily intake of polyphenols in the adult population of Serbia is about 500 mg. It is necessary to increase the daily intake of polyphenols in the adult population in Serbia.